2018
DOI: 10.3390/jmmp2020026
|View full text |Cite
|
Sign up to set email alerts
|

Application of Finite Element Method to Analyze the Influences of Process Parameters on the Cut Surface in Fine Blanking Processes by Using Clearance-Dependent Critical Fracture Criteria

Abstract: The correct choice of process parameters is important in predicting the cut surface and obtaining a fully-fine sheared surface in the fine blanking process. The researchers used the value of the critical fracture criterion obtained by long duration experiments to predict the conditions of cut surfaces in the fine blanking process. In this study, the clearance-dependent critical ductile fracture criteria obtained by the Cockcroft-Latham and Oyane criteria were used to reduce the time and cost of experiments to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…share surface quality is one of the most important factors that provide exibility and stretchability during expansion and anging in the punching process. Therefore, it is an essential criterion in the quality approach of the cutting process [37]- [39]. This study determined that four different regions can be analyzed according to the literature's surface texture and cutting surface.…”
Section: Pierced-punched-sheared Surface and Areas Examinationmentioning
confidence: 99%
“…share surface quality is one of the most important factors that provide exibility and stretchability during expansion and anging in the punching process. Therefore, it is an essential criterion in the quality approach of the cutting process [37]- [39]. This study determined that four different regions can be analyzed according to the literature's surface texture and cutting surface.…”
Section: Pierced-punched-sheared Surface and Areas Examinationmentioning
confidence: 99%
“…The results showed that increased speed results in lower peak force, as a high strain rate enhances adiabatic deformation and ther-mal softening. Myint et al [21] studied the effect of blanking parameters on cut surfaces considering Cockcroft-Latham and Oyane damage models. The Oyane criterion proved more accurate for predicting the fractured profile, while clearance, punch-die radii, initial compression, punch diameter, and stress triaxiality were found to affect the quality of the cut surface.…”
Section: Introductionmentioning
confidence: 99%